Improving Prenatal Care for Minority Women. Issue 3 (May 2016) - Gennaro, Susan; Melnyk, Bernadette Mazurek; O'Connor, Caitlin; Gibeau, Anne M.; Nadel, Ellen
Abstract : Abstract: Since the inception of prenatal care in the early 1900s, the focus of care has been on risk reduction rather than on health promotion. Prenatal care began as individualized care, but more recently group prenatal care has been shown to be very successful in improving birth outcomes. For all women, an emphasis on improving health behaviors is important at this critical time while women are engaging regularly with the healthcare system. An emphasis on mental health promotion may decrease some of the disparities in birth outcomes that are well documented between minority and majority women, as minority women are known to experience increased levels of stress, anxiety, and depression. Providing support for pregnant women and incorporating knowledge and skills through prenatal care may promote both physical and mental health in minority women. Abstract : Prenatal care has traditionally focused on risk reduction rather than health promotion. During prenatal care, childbearing women desire more information on physical and mental health in addition to how to have a healthy pregnancy. Mental health promotion is specially critical for pregnant minority women because they are known to have increased stress, anxiety, and depression, each of which is related to poor pregnancy outcomes.